Family Support in Preventing Mother-to-Child HIV Transmission: A Case Study on the Effectiveness of ARV Therapy in Pregnant Women - Subandi, Eka Ayu Lelyani; Mariyani (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2024)
This study examines the role of family members' knowledge, behavior, and social support in enhancing the effectiveness of antiretroviral (ARV) treatment to prevent mother-to-child HIV transmission at RSUD Ciawi, Bogor. Using a qualitative descriptive approach, data were gathered from December 2023 to January 2024 through in-depth interviews with 11 HIV-positive pregnant women and 11 family members. Findings revealed that most informants adhered well to ARV regimens, with family support, especially from spouses, being crucial. Participants displayed a strong understanding of HIV prevention, favoring cesarean deliveries and formula feeding to reduce transmission risks. However, some emotional challenges, such as stress, fatigue, and economic factors, impeded adherence. The study highlights the necessity of incorporating comprehensive family support into PMTCT programs, addressing medical and emotional needs to improve health outcomes. Despite its insightful findings, the research is limited by its small, localized sample size and the subjective nature of self-reported data. Future studies should investigate the long-term impacts of family support on ARV adherence and mother-to-child transmission rates and develop targeted family education programs to support HIV-positive pregnant women better. The implications for public health practice and policy include the need for a holistic approach to HIV care, integrating family education and support to optimize ARV therapy effectiveness and reduce infant HIV infections.